Beyond Code: the Development of soft skills through Training in Software Engineering - Cavalcante, Victória; Costa, Catarina; Soares, Daricélio (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3541, 2024)
Skills considered non-technical or soft skills, such as communication, teamwork, leadership, problem solving, creativity, adaptability, among others, have become valuable in the development of professional activities. Hiring software professionals has always involved a list of required technical skills, now there is also a list of expectations for professionals who can collaborate with the team more completely. Non-technical skills are typically not the focus of educational institutions, although students are encouraged to work in teams on projects. In this sense, this study investigated the impact of an extension course, which aims to develop technical skills in full-stack web development and the development of soft skills, using active teaching methodologies and agile practices. The study investigated students’ familiarity with Software Engineering concepts and the development of non-technical skills. Two studies, one initial and one at the end of the 7-month course, assessed familiarity with Requirements Engineering, Continuous Delivery and Agile Methods, revealing a significant increase in High Familiarity from 56.7% to 91.5%. There was a significant development of soft skills, with emphasis on the Application of Information Technology (76.2%), Problem Resolution (76.2%), Diversity (76.2%) and Teamwork (71.4%). Furthermore, students highlighted the importance of agile practices and the use of Hands On as main influences for the development and improvement of non-technical skills.